2017
DOI: 10.1007/s12225-017-9728-z
|View full text |Cite
|
Sign up to set email alerts
|

Clarified relationship between Dactylorhiza viridis and Dactylorhiza iberica renders obsolete the former genus Coeloglossum (Orchidaceae: Orchidinae)

Abstract: Summary. Two decades have passed since DNA evidence first demonstrated an intimate relationship between the circumboreal species 'Coeloglossum' viride and the temperate Eurasian genus Dactylorhiza s.s. Most subsequent molecular phylogenies showed 'C.' viride to diverge after the D. incarnata group. The law of monophyly therefore dictated inclusion in Dactylorhiza of 'C.' viride, irrespective of its undeniably distinctive morphology. Those orchid enthusiasts still determinedly seeking reasons for retaining the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In recent years, the fast progress of next-generation sequencing technology has provided a good opportunity for the study of genomic evolution and interspecific relationships of organisms based on large-scale genomic dataset resources, such as complete plastid sequences [ 12 , 13 ]. The chloroplast (cp) is made up of multifunctional organelles, playing a critical role in photosynthesis and carbon fixation [ 5 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the fast progress of next-generation sequencing technology has provided a good opportunity for the study of genomic evolution and interspecific relationships of organisms based on large-scale genomic dataset resources, such as complete plastid sequences [ 12 , 13 ]. The chloroplast (cp) is made up of multifunctional organelles, playing a critical role in photosynthesis and carbon fixation [ 5 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its maternal inheritance and conserved structure characteristics [ 24 , 25 , 26 , 27 ], the cp genomes can provide abundant genetic information for studying species divergence and the interspecific relationships of plants [ 28 , 29 , 30 , 31 ]. For example, based on complete cp genomes, some studies suggested that Dactylorhiza viridis diverged earlier than Dactylorhiza incarnate [ 12 ]; Lepanthes is was distinct from Pleurothallis and Salpistele [ 13 ]. In addition, some researchs based on one nuclear region ( ITS - 1 ) and five chloroplast DNA fragment variations revealed that Bolusiella talbotii and the congeneric B. iridifolia were clustered into an earlier diverged lineage [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such a long proboscis can reach the base of the spur of D. majalis andin the same momentthe viscidium can adhere to the insect's head. The D. majalis spur is a medium-length spur, according to the phylogenetic classification in the Dactylorhiza genus (Adcock et al 1983;De Hert et al 2012;Radak et al 2012;Trunschke et al 2017;Bateman and Rudall 2018). The fit between the D. majalis spur ca.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological features of Dactylorhiza are widely used in the classification of the taxa. The morphological differences in the labellum and spur are widely used to distinguish the taxa (Renz and Taubenheim 1984;Bateman and Rudall 2018). However, the labellum and spur structures can be similar in some of the taxa.…”
Section: Introductionmentioning
confidence: 99%
“…However, this excludes Dactylorhiza viridis (L.) R. M. Bateman, Pridgeon & M. W. which was previously named Coeloglossum viride (L.) Hartm. (Bateman and Rudall 2018). For this reason, it is called as deceptive genus (Claessens and Kleynen 2013).…”
Section: Introductionmentioning
confidence: 99%